2020
DOI: 10.3390/su12062408
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Mainstream Hydropower Dams on Fisheries and Agriculture in Lower Mekong Basin

Abstract: The riverine ecosystems of the Mekong River Basin possess the world’s most productive inland fishery and provide highly productive food crops for millions of people annually. The development of hydropower potential in the Mekong River has long been of interest to governments in the region. Among the existing 64 dams, 46 dams have been built in the Lower Mekong Basin (LMB) to produce up to 8650 MW of electricity. Additionally, of the 123 proposed built hydropower dams, eleven hydropower plants have been nominat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(49 citation statements)
references
References 71 publications
1
47
0
1
Order By: Relevance
“…Overall, we found that the cumulative impacts of reservoir operations and climate change are more sensitive to the magnitude and duration of extreme flow conditions for the 3S basin. In addition, our study confirms that reservoir operations appear to have a considerably stronger impact on the flow regime than climate change [72][73][74]. Furthermore, land use change plays a major role in hydrological alterations [75], but in this study we have limited the analysis of impacts to reservoir operations and climate change.…”
Section: Ha Due To Reservoir Operations and Climate Changesupporting
confidence: 59%
See 1 more Smart Citation
“…Overall, we found that the cumulative impacts of reservoir operations and climate change are more sensitive to the magnitude and duration of extreme flow conditions for the 3S basin. In addition, our study confirms that reservoir operations appear to have a considerably stronger impact on the flow regime than climate change [72][73][74]. Furthermore, land use change plays a major role in hydrological alterations [75], but in this study we have limited the analysis of impacts to reservoir operations and climate change.…”
Section: Ha Due To Reservoir Operations and Climate Changesupporting
confidence: 59%
“…The abundant biodiversity in the basin depends on the natural flood pulse; therefore, changes in the flood pulse may be one of the factors to compromise high biodiversity. Hence, hydrological alterations due to reservoir operations may cause great losses of biodiversity and fisheries in the 3S basin [27,74].…”
Section: Possible Ecohydrological Consequencesmentioning
confidence: 99%
“…This has accelerated the exploitation of wild fish both as broodstock for aquaculture and a premium supply for the ornamental fish market [ 63 ]. Moreover, habitat alteration (e.g., damming or deforestation) and deterioration have been additional threats to these valuable species [ 64 ]. Therefore, it is urgent to gather information on species distribution and diversity to enable proper conservation plans before some species are lost.…”
Section: Geographical Distribution Of Tor Species In the Se Asian Regionmentioning
confidence: 99%
“…The operation of dams in the UMB will be either seasonal or yearly, but all those 11 proposed dams in the LMB are intended for daily operation. However, recently the Upper Mekong River in China is governed by a number of dams and reservoirs, all of which have laid dramatic changes in navigation patterns, the flow of water as well as sediment to the Mekong Delta [40].…”
Section: Study Areamentioning
confidence: 99%